Upcycling spent brewery grains through the production of carbon adsorbents: application to the removal of carbamazepine from water - Sousa, Andreia F. C. (2020)
Spent brewery grains, a by-product of the brewing process, were used as precursor of biochars and activated carbons to be applied to the removal of pharmaceuticals from water. Biochars were obtained by pyrolysis of the raw materials, while activated carbons were produced by adding a previous chemical activation step. The influence of using different precursors (from distinct fermentation processes), activating agents (potassium hydroxide, sodium hydroxide, and phosphoric acid), pyrolysis temperatures, and residence times was assessed. The adsorbents were physicochemically characterized and applied to the removal of the antiepileptic carbamazepine from water. Potassium hydroxide activation produced the materials with the most promising properties and adsorptive removals, with specific surface areas up to 1120 m2 g-1 and maximum adsorption capacities up to 190 ± 27 mg g-1 in ultrapure water. The adsorption capacity suffered a reduction of < 70% in wastewater, allowing to evaluate the impact of realistic matrices on the efficiency of the materials.